KESULITAN BELAJAR PADA PESERTA DIDIK DI SDN 3 KADUAGUNG TIMUR - Ramah Nur Intan; Siti Rokmanah; Patra Aghtiar Rakhman (Jurnal Genta Mulia, 2024)
The problem of this research is based on problems that occur in students who are not yet able to learn well. This research aims to determine the existence of learning difficulties among students at SDN 3 Kaduagung Timur. The method used is a qualitative method. The research technique uses data collection through interviews and observation. Data analysis was carried out using triangulation analysis. The research results show that learning difficulties have an important influence on improving the quality of learning. Learning functions as a forum for sharing knowledge, experience and best practices in the learning process. factors that may cause learning difficulties, methods and strategies that can be used to overcome these problems, as well as the important role that educators, parents and the community must play in helping students overcome these challenges. Learning difficulties are not the end of a person's educational journey, but are the starting point for joint efforts to create an inclusive learning environment and empower each student to achieve their full potential.